Boys don't dance - Carlyna Tambunan Binte Rolan Tambunan (2017)
Director's report for 'Boys Don’t Dance', a narrative film that both questions and celebrates the right of individuality in a conformist and homophobic society through the eyes of a queer boy named Ono.